Potências fracionárias do operador de ondas - Silva, Bosoerg Pereira da (2018)
In this work we study the theory of semigroups of bounded linear operators, the theory of sectorial operators in the sense of Daniel Henry Geometric Theory of Semilinear Parabolic Equations, Lecture Notes in Mathematics, Springer-Verlag, New York Heidelberg Berlin, 1981, the theory fractional power of linear, closed, densely-de?ned operators, and ?nally, we calculate the domain of the fractional powers of the wave operator.